2015
DOI: 10.1002/art.38990
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts in Murine Cutaneous Fibrosis Originate From Adiponectin‐Positive Intradermal Progenitors

Abstract: Objective Accumulation of myofibroblasts in fibrotic skin is a hallmark of systemic sclerosis (SSc; scleroderma), but the origins of these cells remain unknown. Because loss of intradermal adipose tissue is a consistent feature of cutaneous fibrosis, we sought to examine the hypothesis that myofibroblasts populating fibrotic dermis derive from adipocytic progenitors. Methods We performed genetic fate mapping studies to investigate the loss of intradermal adipose tissue and its potential role in fibrosis in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
288
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 280 publications
(310 citation statements)
references
References 49 publications
10
288
2
4
Order By: Relevance
“…6,43 This is further supported by the development of subcutaneous lipoatrophy and concomitant accumulation of fibrous connective tissue at the same location in the mice with adipocyte-specific deletion of PPAR-g. 41,42 A recent cell fate-mapping study that used transgenic mice with adiponectin promoter-driven Cre recombinase to specifically label mature adipocytes also found such a novel link between intradermal adipose loss and dermal fibrosis by showing that adiponectin þ intradermal precursors give rise to dermal myofibroblasts. 29 In this study we report a potential role for FIZZ1 in regulating dermal fibrosis in SSc by targeting the dermal adipocyte and/or its progenitor cell, a suggestion that is supported by in vivo observations of up-regulation of FIZZ2 expression in SSc. 14 …”
Section: Martins Et Al 2774supporting
confidence: 70%
See 1 more Smart Citation
“…6,43 This is further supported by the development of subcutaneous lipoatrophy and concomitant accumulation of fibrous connective tissue at the same location in the mice with adipocyte-specific deletion of PPAR-g. 41,42 A recent cell fate-mapping study that used transgenic mice with adiponectin promoter-driven Cre recombinase to specifically label mature adipocytes also found such a novel link between intradermal adipose loss and dermal fibrosis by showing that adiponectin þ intradermal precursors give rise to dermal myofibroblasts. 29 In this study we report a potential role for FIZZ1 in regulating dermal fibrosis in SSc by targeting the dermal adipocyte and/or its progenitor cell, a suggestion that is supported by in vivo observations of up-regulation of FIZZ2 expression in SSc. 14 …”
Section: Martins Et Al 2774supporting
confidence: 70%
“…Therefore, FIZZ1 could cause dedifferentiation of adipocytes followed by differentiation into myofibroblasts in vitro, consistent with a role in adipocyte transdifferentiation to the myofibroblast, a key cell in pathogenesis of chronic fibrosis. 4,29 However, because FIZZ1 caused incomplete (<60%) inhibition of adipocyte gene marker expression, direct adipocyte-to-myofibroblast transdifferentiation without going through a dedifferentiated state cannot be ruled out.…”
Section: Adipocyte Dedifferentiation and Myofibroblast Differentiationmentioning
confidence: 99%
“…An important question for the future is how these stresses alter the expression of PDGF ligands or PDGFRα signaling in a manner that would cause progenitors to transition into profibrotic cells. Intriguingly, a recent study suggested that profibrotic cells in the skin can transition from adiponectin-expressing cells or mature adipocytes in the context of bleomycin-induced fibrosis (Marangoni et al 2015). Although mature adipocytes do not express PDGFRα under normal conditions, its reexpression in disease states could be important.…”
Section: Discussionmentioning
confidence: 99%
“…Dermal adipocytes form a stand-alone depot, distinct from SAT ( Fig. 1) (Driskell et al, 2014;Festa et al, 2011), with potential functions in hair follicle cycling, wound healing and bacterial infection (Alexander et al, 2015;Festa et al, 2011;Marangoni et al, 2015;Zhang et al, 2015). Further studies are needed to elucidate the metabolic role of dermal adipose tissue.…”
Section: Adipose Tissue Depotsmentioning
confidence: 99%